2013
DOI: 10.1182/blood-2013-01-478073
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 is produced by afferent lymphatic vessels and supports lymphatic drainage

Abstract: Key Points• Afferent lymphatic vessels express interleukin-7.• Interleukin-7 supports lymphatic drainage.The cytokine interleukin (IL)-7 exerts essential roles in lymph node (LN) organogenesis and lymphocyte development and homeostasis. Recent studies have identified lymphatic endothelial cells (LECs) as a major source of IL-7 in LNs. Here, we report that LECs not only produce IL-7, but also express the IL-7 receptor chains IL-7Ra and CD132. Stimulation with recombinant IL-7 enhanced LEC in vitro activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 49 publications
4
66
0
3
Order By: Relevance
“…As we used adoptive transfer of 1 × 10 7 effector Th2 cells to address the role of IL-7 for maintenance of memory Th2 cells, it is still possible that in vivo-generated smaller numbers of memory Th2 cells are less reliant on IL-7. In addition, it is reported that IL-7 exerts an important role in lymph node organogenesis and promoting lymphatic drainage (45). Less iBALT development and decreased memory T-cell accumulation detected in Tie2-Cre + Il-7 fl/fl mice could also be caused by indirect effects on lymphocyte trafficking or Th2 cell activation and maintenance in the mediastinal lymph node, or on various stromal cell structures needed for migration or retention of memory Th2 cells within iBALT.…”
Section: Discussionmentioning
confidence: 99%
“…As we used adoptive transfer of 1 × 10 7 effector Th2 cells to address the role of IL-7 for maintenance of memory Th2 cells, it is still possible that in vivo-generated smaller numbers of memory Th2 cells are less reliant on IL-7. In addition, it is reported that IL-7 exerts an important role in lymph node organogenesis and promoting lymphatic drainage (45). Less iBALT development and decreased memory T-cell accumulation detected in Tie2-Cre + Il-7 fl/fl mice could also be caused by indirect effects on lymphocyte trafficking or Th2 cell activation and maintenance in the mediastinal lymph node, or on various stromal cell structures needed for migration or retention of memory Th2 cells within iBALT.…”
Section: Discussionmentioning
confidence: 99%
“…Without local lymphatic vessels and their associated drainage, peripherally activated dendritic cells (DCs) cannot traffic to the dLNs to activate immune responses (6), and LN resident immature DCs are not exposed to lymph-borne self-antigens released from extracellular proteases and apoptotic cells for tolerogenic presentation to autoreactive T cells (7,8). Additionally, lymphatic endothelial cells (LECs) themselves can contribute to regional immunity in other ways, including active regulation of fluid drainage (9), direct modulation of DC trafficking and activation (10,11), cellular egress leading to immune resolution (12,13), and direct suppression of lymphocyte activation through steady-state presentation of endogenous self antigens (14) or cross-presentation of draining exogenous antigens (7,15,16). Importantly, lymphangiogenesis is seen in a host of inflammatory situations, including melanoma and other cancers (1,17).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, these cells continued to grow as monolayers, implying that HOXD10 is required for the morphological changes LECs undergo while forming tube-like structures. Overexpression of HOXD10 resulted in the dysregulation of several genes previously implicated in (lymph-) angiogenesis and vascular morphogenesis, including DLL4 (Niessen et al, 2011;Zheng et al, 2011), IL7 (Iolyeva et al, 2013), AMOTL2 (Hultin et al, 2014), ROBO4 (Yu et al, 2014) and PTPRB (also called VE-PTP) (Hayashi et al, 2013), indicating that these genes are direct or indirect targets of HOXD10. In line with our hypothesis that HOXD10 is only required in acutely stimulated cells, we did not see any changes in the expression of these genes in unstimulated LECs after HOXD10 knockdown.…”
Section: Discussionmentioning
confidence: 98%